Hip Joint Rotational Movement Range in the Course of Femoroacetabular Impingement Among Individuals Practising Recreational Long-Distance Running - Robert Walaszek; Wiesław Chwała; Katarzyna Burdacka; Marcin Burdacki; Paweł Kurowski (Rehabilitacja Medyczna)
Introduction: Changes in hip joint morphology include distortions, deformities or abnormalities in the anatomy that can affect its function and cause pain.Objectives: The aim of the study was to assess the effect of a six-month therapeutic intervention on changes in the range of rotational movements in the hip joints among individuals with femoroacetabular impingement practising recreational long-distance running.Material and methods: The study involved 44 men, aged 30 to 50 years. Two runs of tests were conducted in the Laboratory of Biokinetics, University of Physical Education (now: University of Physical Culture) in Kraków. The first measurements were carried out in January 2020, and the second ones – in July 2020. Examination of hip joint internal rotation (ROMIN) and external rotation (ROMEX) ranges was carried out using a BOSCH electronic goniometer.Results: The mean values of internal rotation and external rotation ranges measured during the second examination were significantly higher than the results of the first examination, both in the experimental and control groups. Both before and after the therapeutic intervention, some statistically significant differences were found in the mean values of internal rotation (ROMIN) range between runners with FAI (femoroacetabular impingement) and n-FAI (non-femoroacetabular impingement) runners. No such relationships were found in the range of external rotation (ROMEX).Conclusions: After the intervention, the mean values of the analysed runners with FAI approached the values observed in the control group. The results of the conducted research enable practical use of the proposed comprehensive proprietary intervention in the conservative treatment of physically active people with FAI.